Novel management to enhance spider biodiversity in existing grass buffer strips. (7th November 2012) - Blake, Robin J.; Woodcock, Ben A.; Westbury, Duncan B.; Sutton, Peter; Potts, Simon G.
<x xml:space="preserve">Abstract</x> 1 Grass buffer strips have been widely sown to mitigate against intensive agricultural management practices that have negatively impacted on invertebrate and plant biodiversity in arable farming systems. Typically, such strips are floristically species poor and are dominated by grasses. In the present study, we developed management practices to enhance the floristic and structural diversity of these existing strips for the benefit of spiders, a key provider of natural pest control in crops. 2 Across three UK arable farms, we investigated the benefits of: (i) scarification to create germination niches into which wildflower seeds were sown and (ii) the effect of graminicide applications to suppress grass dominance. Spiders were sampled twice per year (July and September) during 2008 and 2009. 3 The combination of scarification with wildflower seeds, as well as graminicide, resulted in the greatest wildflower cover and lowest grass cover, with a general trend of increased abundance of adult and juvenile spiders. The abundance of Pachygnatha degeeri, Bathyphantes gracilis and juvenile wolf spiders of the genus Pardosa was positively correlated with wildflower cover, probably reflecting increased prey availability. Sward structure was negatively correlated with Erigone atra, Oedothorax fuscus and juvenile Pardosa abundance. 4 Management that utilizes existing commonly adopted agri‐environment options, such as grass buffer strips, represents a potentially important conservation tool for increasing the quantity and quality of invertebrate habitats. This can maximize opportunities for the provision of multiple ecosystem services, including pest regulation by predators such as spiders. These management practices have the potential to be incorporated into existing U.K. and European agri‐environment schemes.